Identifying challenges in implementing sustainable practices in a developing nation - Saadatian, Omidreza; Mohd Tahir, Osman; Dola, Kamariah (Canadian Center of Science and Education, 2010)
The South Pars Special Economic Energy Zone (SPSEEZ) is the largest petroleum zone in Iran and the second biggest gas producer in the world. It is now one of the world’s most important eco-industrial poles. Despite the rapid development and activists’ calls to sustainable path, there is little systematic effort in the assessment of industrial zones sustainability in developing countries. Iran, a nation that has ratified the Rio Declaration pact, has moved forward in order to achieve sustainable development. There have always been controversial debates due to its success. This paper employs survey, interview as well as observation to explore the perception of people on planning and sustainable development efforts and to identify the most important challenges at SPSEEZ. The result shows that the major impediment against sustainability is the lack of involvement from urban planners and the public during decision-making process. Finally, the paper contributes to the identification of the most urgent problems in SPSEEZ and the functions of different stakeholders as a reference for better sustainable development planning.